A Hybrid Lossless Encoding Method for Compressing Multispectral Images using LZW and Arithmetic Coding - Boopathiraja, S; Kalavathi, P; Chokkalingam, S (International Journal of Computer Sciences and Engineering, 2018)
Most of the remote sensing images are multispectral image where these images are acquired in the form of several bands that constitute a spectral direction. As large amount of data is represented by multispectral image, a lot of memory space is needed for storage and transmission. Hence, there is big need for compression methods for multispectral images. The prime factor of any image compression method is the redundancy as well as correlation on an image. In this way, the multispectral images having high degree of correlation on spatial domain and redundancy on spectral domain. This leads to conception of several compression methods for these multispectral images. Moreover, every tiny information from multispectral image is very important for efficient processing and so the lossless encoding is always preferable. In this paper, we proposed a hybrid lossless method using Lempel-Ziv-Welch (LZW) and Arithmetic Coding for compressing the multispectral Images. The performance of our method is compared with existing lossless compression methods such as Huffman Coding, Run Length Coding (RLE), LZW and Arithmetic Coding.